Brief report of a field investigation in Noto Peninsula, Japan, after the 2024 Noto earthquake - Xingliang Peng; Fawu Wang; Masakatsu Miyajima; Masaho Yoshida; Shuai Zhang; Zijin Fu (Geoenvironmental Disasters)
Abstract On January 1, 2024, a shallow reverse faulting event occurred in the Earth’s crust on the west coast of Suzu City, on the Noto Peninsula of Ishikawa Prefecture, Japan, and triggered a strong earthquake (Mw 7.5). The shaking and accompanying tsunami hit the Noto Peninsula, causing significant fatalities and economic losses. Four months after the earthquake, the International Consortium on Geo-disaster Reduction (ICGdR) organized a post-earthquake geohazard field investigation with the participation of the ICGdR director-general and the ICGdR presidents and their assistants. The four-day field investigation was conducted from May 1 to May 4, 2024, and focused specifically on earthquake-induced landslides, landslide dams, and coastal uplifts along the most devastated areas (i.e., Wajima City and Suzu City, passing through Nanao City and Housu District). A large amount of original seismic, geological, topographic, and hydrological data was collected during this investigation, with the aim of analyzing the mechanism of earthquake-induced geohazards and providing further insight into disaster mitigation.